Insulin-like growth factor 2 hypermethylation in peripheral blood leukocytes and colorectal cancer risk and prognosis: a propensity score analysis - Sun, HongRu; Liu, YanLong; Zhang, YuXue; Wang, Yibaina; Zhao, YaShuang; Liu, YuPeng (Frontiers in Oncology, 2023)
Abstract Background: To comprehensively assess and validate the associations between insulin-like growth factor 2 (IGF2) gene methylation in peripheral blood leukocytes (PBLs) and colorectal cancer (CRC) risk and prognosis. Methods: The association between IGF2 methylation in PBLs and CRC risk was initially evaluated in a case-control study and then validated in a nested case-control study and a twins’ case-control study, respectively. Meanwhile, an initial CRC patient cohort was used to assess the effect of IGF2 methylation on CRC prognosis and then the finding was validated in the EPIC-Italy CRC cohort and TCGA datasets. A propensity score (PS) analysis was performed to control for confounders, and extensive sensitivity analyses were performed to assess the robustness of our findings. Results: PBL IGF2 hypermethylation was associated with an increased risk of CRC in the initial study (ORPS-adjusted, 2.57, 95% CI: 1.65 to 4.03, P<0.0001), and this association was validated using two independent external datasets (ORPS-adjusted, 2.21, 95% CI: 1.28 to 3.81, P=0.0042 and ORPS-adjusted, 10.65, 95% CI: 1.26 to 89.71, P=0.0295, respectively). CRC patients with IGF2 hypermethylation in PBLs had significantly improved overall survival compared to those patients with IGF2 hypomethylation (HRPS-adjusted, 0.47, 95% CI: 0.29 to 0.76, P=0.0019). The prognostic signature was also observed in the EPIC-Italy CRC cohort, although the HR did not reach statistical significance (HRPS-adjusted, 0.69, 95% CI: 0.37 to 1.27, P=0.2359). Conclusions: IGF2 hypermethylation may serve as a potential blood-based predictive biomarker for the identification of individuals at high risk of developing CRC and for CRC prognosis.